Metastatic multiple endocrine neoplasia type 1: report of one case - Huang, Cheng; Zhu, Xiaodong; Han, Xu; Lou, Wenhui (Translational Gastroenterology and Hepatology, 2016)
A 46-year-old Chinese woman was admitted to our hospital because of presence of space-occupying lesions in the liver for 2 months in April, 2015. She had a family history of multiple endocrine neoplasia type 1 (MEN1) and physical examination is unremarkable. Previously, she has performed surgery for primary pituitary tumor in 2002 and radiosurgery for its recurrence. Around December 2014, she suffered from abdominal discomfort associated with regurgitation and gastroscopy revealed “gastroduodenal ulcers”, along with elevated gastrin. Next, both magnetic resonance and computed tomography imaging showed multiple intrahepatic lesions, the PET-CT unveiled uptake pattern of 18F-FDG in duodenum and multiple intrahepatic lesions, resembling the appearance of metastatic gastrinoma. The octreotide scan gave identical results. The parathyroid SPECT scans showed abnormal concentrations of radioactivity in right parathyroid. She also had an elevated serum chromogranin A (CgA) level. There was medical evidence to show that she is metastatic MEN1. Although multiple liver metastases, they were considered to be resectable after MDT consultation. The intraoperative exploration found a 1.5 cm tumor on the surface of the tail of the pancreas, a 12 cm retroperitoneal lipoma and two liver metastases, sized 3.5 cm and 1.5 cm, respectively. All these tumors were completely removed. For pancreatic tumor, pathological findings met the diagnostic criteria of neuroendocrine tumor (NET) (G2). Immunohistochemistry revealed neuroendocrine areas were diffusely positive for ATRX, DAXX, SSR2, SSR5 and CgA. For lipoma, the FISH results were negative for CDK4 and MDM2 genes. Postoperatively, adjuvant therapy with octreotide was applied. This case suggested that, as for metastatic gastrinoma, a potentially curative surgical debulking should be considered when a resection of complete or more than 90% of metastatic lesions along with the primary site could be achieved, which is helpful to control symptoms and delay the subsequent need for therapy.